EFEKTIVITAS MEDIA JARIMATIKA TERHADAP HASIL BELAJAR SISWA PADA MATERI PERKALIAN - Mandasari, Lola; Asnawi, Asnawi (Ta'dib: Jurnal Pemikiran Pendidikan, 2022)
Education is a need for every individual, which is obtained through the learning process. One of the lessons is mathematics, but learning mathematics is still hampered by several problems, one of which is the low student learning outcomes. To help students in learning mathematics, various kinds of media can be used, one of which is media that can help students in learning. This study aims to examine whether there are learning outcomes in mathematics using the media of jarimatika at MIN 9 Central Aceh. This type of research is descriptive quantitative. The population of this research is all students of class V MIN 9 Central Aceh for the 2021-2022 academic year. The sample consisted of 34 students, the sample in this study was determined using cluster random sampling. Research data collection was carried out by observation, questionnaires, tests, and documentation. Based on research that has been conducted in class V MIN 9 Central Aceh, it shows that there is an influence from the use of multimedia media from the research results that 90.90% of students complete classically. The results of observing student activity yielded 77.5% in the good category. And the average score obtained from the distribution of student response questionnaires is 82 in the good category. From the results of the research above, it can be concluded that the media of media is effectively used in learning mathematics for class V students on multiplication material at MIN 9 Central Aceh